69.7k views
2 votes
I need help on this, please explain how you get the result.

I need help on this, please explain how you get the result.-example-1

1 Answer

4 votes

Answer:


x=5

Explanation:

We have the equation:


34\cdot 3^(x-2)-2\cdot 3^(x-3)=0.8\cdot 10^(x-2)+10^(x-3)

Let's simplify this a bit. Let
u=x-2. Then
u-1=x-3. We can substitute the exponents:


34\cdot3^u-2\cdot 3^(u-1)=0.8\cdot 10^u+10^(u-1)

Use the properties of exponents, we can write
3^(u-1)=(3^u)/(3). We can do the same thing on the right. So:


34\cdot3^u-2\cdot (3^u)/(3)=0.8\cdot 10^u+(10^u)/(10)

We can now factor out a
3^u from the left and a
10^u on the right. This yields:


3^u(34-2\cdot(1)/(3))=10^u(0.8+ (1)/(10))

Evaluate the expressions within the parentheses:


3^u(34-(2)/(3))=10^u((9)/(10))

Evaluate:


3^u((100)/(3))=10^u((9)/(10))

Now, let's multiply both sides by
(3)/(100). So:


3^u=10^u((9)/(10))((3)/(100))

Also, let's divide both sides by
10^u. Multiply on the right:


(3^u)/(10^u)=(27)/(1000)

Therefore:


3^u=27\text{ and } 10^u=1000

We can now substitute back u. Notice that 27 is the same as 3 cubed and 1000 is the same as 10 cubed. So:


3^(x-2)=3^3\text{ and } 10^(x-2)=10^3

Since they have the same base, their exponents must be equal. Therefore:


x-2=3

Add 2 to both sides:


x=5

So, the value of x is 5.

And we're done!

User Jtorca
by
5.7k points